(untitled) - Jacob, J. Michael (Victoria, 2004)
From the moment they open Advanced AC Electronics: Principles and Applications, readers will become actively involved in learning how to apply AC circuit techniques to electronics circuits that are interesting and actually do something useful! Rather than presenting AC electronics as a series of seemingly magical rules and incantations, this book integrates AC circuit theory tools with electronics, interweaves topics as needed, and introduces the use of circuit analysis tools on a just-in-time basis to support development of electronics circuits. It engages readers in applying circuit theory to a wide variety of passive and active electronics that respond to a sinusoidal signal with both a change in magnitude and a shift in the sine wave's phase. Immediately upon introduction, each technique is applied to a host of examples, including: commercial electrical power production and distribution, industrial motor performance and control, audio systems, instrumentation, radio frequency, and communications circuits. Motors, rf and audio cables, loudspeakers, thyristors, transition and op amp amplifiers are also introduced early on, capturing attention while guiding readers in their examination of real-world responses to sinusoids. Level and rigor make Advanced AC Electronics an ideal choice for programs accredited by the Accreditation Board for Engineering and Technology (ABET).
Keywords: Electric circuits,Electronics; Alternating current,Problems, exercises, etc,Problems, exercises, etc